ANALYSIS OF INDONESIAN NATIONAL DATA FOR RELATIONSHIP BETWEEN PREVALENCE OF HYPERTENSION, PHYSICAL ACTIVITY, AND HIGH-RISK FOOD CONSUMPTION WITH STROKE PREVALENCE - Haq, Nabiila Ala Qoonita Najma; Ernanda, Shelby Amrus; Marhaendraputro, Eko Arisetijono (Journal of Pain, Headache and Vertigo, 2025)
physical activity, and high-risk food consumption. This study aimed to analyze the relationship between these risk factors and stroke prevalence across Indonesia, using data from the Indonesian Health Survey covering 514 districts/cities in 38 provinces. The analysis focused on hypertension prevalence, physical activity levels, and dietary habits (particularly high salt intake). Spearman correlation results showed a significant association between hypertension and stroke prevalence (P < 0.001, r² = 0.451). In contrast, no significant association was found between low physical activity and stroke (P = 0.161, r² = 0.05), nor between high salt intake and stroke (P = 0.110, r² = 0.06). In conclusion, the study confirms that hypertension is significantly associated with an increased risk of stroke in Indonesia, emphasizing the need for interventions targeting hypertension to reduce stroke cases nationwide. While low physical activity and risky dietary habits did not show strong associations with stroke prevalence, these factors still warrant attention.